Port-centric cities: The role of freight distribution in defining the port-city relationship. (January 2018) - Monios, Jason; Bergqvist, Rickard; Woxenius, Johan
Abstract: The goal of this paper is to explore the intersection between two streams of literature: port cities and port-centric logistics. While many ports have moved out of city locations, partly facilitated by intermodal corridors, some ports remain in city locations, many retaining a large share of distribution activity in or near the port. This paper will consider distribution challenges arising from the port-city dynamic in relation to the port-inland distribution axis, in particular the role of port and city planners and decision makers in managing this process. The case analysis is based on the Port of Gothenburg, the largest port in Scandinavia. Findings suggest that the majority of influencing factors are marginally in favour of siting distribution facilities inland rather than near the port, yet city planning and national sentiment continue to incentivise development near the port. There are two conclusions for the port-centric city. First, it needs to coordinate its logistics from a regional perspective, determine what activities belong near the port and not compete with inland locations for what is better located there. Second, port-centric logistics needs to be better aligned with an urban freight transport and city logistics perspective.